The Digital Paradox: A Longitudinal Multi-Level Analysis of Social Media Engagement Intensity and Psychological Distress Trajectories Among Indonesian Adolescents (2022–2025) - Vita Amanda; Jason Wilmare; Sonia Vernanda (Open Access Indonesia Journal of Social Sciences, 2025)
The rapid digital transformation in Indonesia has positioned social media as a primary socialization agent for adolescents. However, the psychological cost of this connectivity remains poorly understood in the context of long-term exposure. This study examines the longitudinal relationship between social media intensity (SMI) and psychological distress among Indonesian youth. A multi-level longitudinal design was employed, tracking a cohort of 4,500 adolescents aged 12 to 18 across 12 urban and rural provinces in Indonesia from 2022 to 2025. Data were collected bi-annually using the Social Media Intensity Scale (SMIS) and the Kessler Psychological Distress Scale (K10). Multi-level modeling (MLM) was utilized to account for the nested structure of data, specifically observations within individuals nested within provinces. Results indicated a significant U-shaped curvilinear relationship between SMI and psychological distress. While moderate use was associated with lower distress through social capital, high-intensity usage—defined as more than 5 hours daily—predicted a 42% increase in K10 scores (p<0.001). Socio-economic status and urbanicity significantly moderated these effects, with rural youth showing higher vulnerability to digital social comparison. In conclusion, excessive social media connectivity acts as a significant stressor for Indonesian adolescents. Intervention strategies must transition from simple screen-time restriction to nuanced digital resilience training that considers regional socio-economic disparities.